2012
DOI: 10.1175/jcli-d-11-00170.1
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling the Spatial Distribution of the Surface Temperature Trends in the Southeastern United States

Abstract: This study attempts to explain the considerable spatial heterogeneity in the observed linear trends of monthly mean maximum and minimum temperatures (T max and T min ) from station observations in the southeastern (SE) United States (specifically Florida, Alabama, Georgia, South Carolina, and North Carolina). In a majority of these station sites, the warming trends in T min are stronger in urban areas relative to rural areas. The linear trends of T min in urban areas of the SE United States are approximately 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 39 publications
1
48
1
1
Order By: Relevance
“…This has been used in the past for land cover change studies. 13,14 PIZA essentially indexes the influence of urban-related activities (including residential, commercial, and industrial) on agricultural land use. The PIZA code is derived from population-interaction index (PII), which provides a measure of potential interaction between nearby urban-related population and agricultural production activities, by effectively ranking each location or an area on a continuous scale from 1 to 4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been used in the past for land cover change studies. 13,14 PIZA essentially indexes the influence of urban-related activities (including residential, commercial, and industrial) on agricultural land use. The PIZA code is derived from population-interaction index (PII), which provides a measure of potential interaction between nearby urban-related population and agricultural production activities, by effectively ranking each location or an area on a continuous scale from 1 to 4.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10] There have been a number of studies that have indicated the impact of land cover change on local climate. [11][12][13][14] For example, Marshall 15 found that drainage and conversion of wetlands to agricultural land could increase the likelihood of the frequency, severity, and duration of freezes in south Florida. Similarly, Misra et al 13 found that the temperature trends for urban and rural regions of the southeastern US were different because of the contrasting impact of the land cover types in the two regions.…”
Section: Introductionmentioning
confidence: 99%
“…S i n c e t h e s t r e n g t h of these atmospheric teleconnections are linearly dependent on the equatorial Pacific SST anomalies (Kumar and Hoerling 1998), it is reasonable to expect these teleconnections to be modulated by variations in the amplitude of ENSO SST anomalies (Diaz et al 2001). Using observations, several studies have shown that the positive (negative) phase of AMO weakens (enhances) the ENSO teleconnection with the SEUS rainfall (Enfield et al 2001;Mo 2010;Misra et al 2012;Nag et al 2015). Similarly, Diaz et al (2001) indicated ENSO teleconnections with North America have intensified post-1976.…”
Section: Enso Variabilitymentioning
confidence: 99%
“…We have, therefore, restricted discussions in this chapter to variations that could be reasonably resolved in the past 100 years. However, it is a challenge to isolate natural variability of climate when artificially-introduced variations from changes in location of observation, instrumentation, and method of measurement are not accounted for (Misra and Michael 2012). In addition, complex interactions in natural climate variation across space and time, as well as anthropogenic climate change, make understanding the manifestation of specific climate anomalies and weather events difficult.…”
Section: Introductionmentioning
confidence: 99%
“…(Yun, 2002;Chung et al, 2004;O'Hare et al, 2005;Ahn et al, 2010;Hu and Jia, 2010;Middel et al, 2012;Misra et al, 2012;Li et al, 2013).…”
mentioning
confidence: 99%